(untitled) - Jastrow, Robert (New York, 1977)
This wonderful book should be back in print. It is a readable (and beautiful) college-level introduction to the basic ideas, concepts, and history of this fascinating science. It is perfectly accessible for the layman -- and even for those previously unfamiliar with Astronomy
Keywords: Astronomy